Pengaruh Perputaran Kas terhadap NPM pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia - Irvan Firmansyah Maulana; Hasbi Assidiki Mauluddi; Banter Laksana (Indonesian Journal of Economics and Management, 2022)
The research in this final project aims to determine and analyze the effect of cash turnover on the Net Profit margin in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2012-2018. The type of data used is secondary data in the form of the company's annual financial statements. In this study, there are 5 food and beverage companies on the Indonesia Stock Exchange that are used as research samples. The research method used is descriptive and quantitative research. The test was carried out by means of the Determination Coefficient test which was processed using SPSS 26. The panel data regression method selected was Simple Linear Regression. The results showed that cash turnover had a negative effect on Net Profit Margin.